E-Health Literacy Skills in Hypertension Sufferers (HEALTH CARE: JURNAL KESEHATAN, 2024)
Hypertension is a type of chronic disease with high morbidity and mortality rates and can be reduced by implementing self-management. Success in managing hypertension can be done with the individual's ability to find information. Efforts to obtain information related to health care are carried out by utilizing information technology in the form of the internet. Individual efforts to access information related to treatment and health care through the internet is called e-health literacy. The purpose of this research is to determine the ability of e-health literacy in hypertensive patients in working area of the Rejosari Health Center. This research is quantitative with a descriptive research design. A sample of 90 respondents used a purposive sampling technique. The instrument used is an e-heals questionnaire which has been tested for validity and reliability. The results of the research illustrate that the majority of respondents had low e-health literacy as many as 51 people (56,7%) and high e-health literacy as many as 39 people (43,3%).